Effect of calcination conditions on phase formation and particle size of nickel niobate powders synthesized by solid-state reaction - O. Khamman (2018)
The solid-state mixed oxide method via a rapid vibro-milling technique is explored in the preparation of single-phase nickel niobate (NiNb2O6) powders. The formation of the NiNb2O6phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM and EDX techniques. It has been found that the minor phases of unreacted NiO and Nb2O5precursors and the Ni4Nb2O9phase tend to form together with the columbite NiNb2O6phase, depending on calcination conditions. More importantly, it is seen that optimization of calcination conditions can lead to a single-phase NiNb2O6in an orthorhombic phase. © 2006 Elsevier B.V. All rights reserved.